Defective cytokine production early after multiple traumas: Modulation in severe sepsis. Issue 2 (December 2015) - Paraschos, Michael D.; Patrani, Maria; Pistiki, Aikaterini; Katsenos, Chrysostomos; Tsaganos, Thomas; Netea, Mihai G.; Giamarellos-Bourboulis, Evangelos J.; Mandragos, Konstantinos
Highlights: There is a significant down-regulation of innate immune responses after severe injury. Over-production of interferon-gamma is linked with trauma-related multiple organ failure. Transition to severe sepsis is accompanied by over-production of tumour necrosis factor-alpha. Abstract: The exact time frame of multiple trauma-induced immunosuppression and the immune mechanisms mediating transition to severe sepsis are largely unknown. Peripheral blood mononuclear cells were isolated from 69 patients with multiple injuries within the first 24 h from injury and from 36 healthy volunteers and stimulated for cytokine production. Circulating endotoxins were measured by the kinetic LAL assay. Measurements were repeated the first 24 h of sepsis onset. Patients had defective responses for tumour necrosis factor-alpha (TNFα), interleukin (IL)-10, IL-17 and interferon-gamma (IFNγ) using a broad-panel of bacterial stimuli. Production of IFNγ was pronounced for patients with trauma-related multiple organ failure (MOF). Thirty-six patients developed severe sepsis. At that time, production of TNFα was increased compared to baseline. The increase was greater among non-survivors than among survivors. Enhanced TNFα production on sepsis onset was a main finding of patients without endotoxemia. Immunosuppression of both innate and adaptive cytokine responses appears as early as the first 24 h from injury. Transition into severe sepsis due to bacterial superinfection is accompanied by enhanced production of TNFα and this is linked with unfavorable outcome.